Evaluation of Positron Emission Tomographic Tracers for Imaging of Papillomavirus-Induced Tumors in Rabbits - Sonja Probst; Stefan Wiehr; Frederic Mantlik; Holger Schmidt; Armin Kolb; Peter Münch; Maria Delcuratolo; Frank Stubenrauch; Bernd J. Pichler; Thomas Iftner (Molecular Imaging)
In this study, simultaneous positron emission tomography (PET)/magnetic resonance (MR) imaging was employed to evaluate the feasibility of the PET tracers 2-deoxy-2- 18 F-fluoro-D-glucose ( 18 F-FDG), 11 C-choline, and 18 F-fluorothymidine ( 18 F-FLT) to detect papillomavirus-induced tumors in an established rabbit model system. The combined PET/MR allowed the analysis of tracer uptake of the tumors using the morphologic information acquired by MR. New Zealand White rabbits were infected with cottontail rabbit papillomavirus genomes and were imaged for up to 10 months with a simultaneous PET/MR system during the course of infection. The uptake characteristics of the PET tracers 11 C-choline and 18 F-FLT of tumors and reference tissues were examined relative to the clinical standard, 18 F-FDG. Tracer biodistribution of various organs was measured by gamma-counting after the last PET scan and compared to the in vivo PET/MR 18 F-FDG uptake. Increased tracer uptake was found 2 months postinfection in primary tumors with 18 F-FDG and 11 C-choline, whereas 18 F-FLT failed to detect the tumors at all measured time points. Our data show that the PET tracer 18 F-FDG is superior for imaging papillomavirus-induced tumors in rabbits compared to 11 C-choline and 18 F-FLT. However, 11 C-choline imaging, which has previously been applied to detect various tumor entities in patients, appears to be an alternative to 18 F-FDG.